Komunikasi Interpersonal Perawat Pada Pasien Penyandang Disabilitas Mental di Sentra Phala Martha Sukabumi - Sari, Anitta Shaila; Destiwati, Rita (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This interpersonal communication plays an important role in the daily interactions between nurses and their patients. The role of the nurse is very influential on the conditions of those with mental disabilities who are being rehabilitated. The most effective interpersonal communication used by nurses in approaching patients with mental disabilities at the Phala Martha Sukabumi Center. This research is to find out the nurse's interpersonal communication between patients with mental disabilities at the Phala Martha Sukabumi Center. This research found that at the stage of social penetration theory is an effective exchange of various information exchanges as well as in Social Penetration activities. This primary data was obtained from observation, interviews, and documentation. This research method uses a qualitative research method that examines the condition of an object. The results showed that the Interpersonal Communication of Nurses in patients with Mental Disabilities at the Phala Martha Sukabumi Center established good communication relationships. Communication between nurses and patients with mental disabilities is an interpersonal approach. With this stage of the nurse's approach to building a relationship of mutual trust is one of opening patients to be open to nurses, and a supportive attitude by providing positive encouragement for patients who are relapsed during rehabilitation.